Analysis of the usability of treated wastewater for fire protection purposes - Ondrasik, Frantisek; Krocova, Sarka (European Journal of Chemistry, 2023)
Current water management does not fully account for potential crisis situations when dealing with drinking water. It is important to focus on an efficient and at the same time economic approach to water management, including consideration of the ecological aspect. One way is to focus on the use of alternative sources of water. The possibilities of purified wastewater or captured rainwater indicate a certain direction. Current technical possibilities and scientific knowledge offer many opportunities. The priority is to find and increase the way to limit the use of drinking water for economic activities. The more intensive use of alternative water sources is still in the background and neglected. This article provides information on this issue and encourages deeper ecological and economic reflexion.